Pharmaceutical supply chain management: Ensuring quality and security in the distribution of medicines - Alshameri, Mariam Sabr; Alotaibi, Samar Saad; Almutairi, Nawal Hlal; Bahari, Nawal Ganai M; Almutairi, Alhanouf Zaid; Alharbi, Faisal Nasser; Almasad, Manal Nasser; Alqarni, Zainab Ali; Almazroa, Mashaal Nasser (International journal of health sciences, 2022)
Background: The globalization of pharmaceutical supply chains has exposed significant vulnerabilities, enabling counterfeit medications to infiltrate the market. These counterfeit drugs not only fail to aid in the recovery of patients but also pose serious health risks due to their inferior quality. The World Health Organization (WHO) reports that in developing nations, approximately 10% of medications consumed by patients are counterfeit. This alarming statistic, coupled with the estimated annual loss of over 200 billion faced by US pharmaceutical companies, underscores the urgent need for an effective monitoring solution to safeguard against counterfeiting. Aim of Work: The primary aim of this study is to develop a robust drug supply chain management and recommendation system (DSCMR) that leverages blockchain technology and machine learning to ensure the integrity of medications throughout the supply chain while providing consumers with effective medication recommendations. Methods: The proposed DSCMR comprises two main modules: Blockchain-Based Drug Supply Chain Management: This module uses Hyperledger Fabric to create a secure and transparent system for monitoring and tracing the delivery of medications through the supply chain. This technology ensures that all transactions are recorded and verifiable, enhancing trust in the pharmaceutical process.